La energía como indicador del impacto ambiental en los sistemas constructivos conformados a partir de materiales de producción nacional - Casañas Muniz, María Virginia (2011)
Energy consumption is one of the most important environmental issues facing contemporary society. The energy used in homes and buildings comes mainly from burning fossil fuels (oil, natural gas and coal) which contribute significantly to air pollution. The construction industry worldwide is responsible for 50 % of natural resources and 40 % of energy consumption, considering the same in the Lifecycle Building: energy in the manufacture of buildings materials, in the life of the building, in the work itself and in the deconstruction of it. The challenge ahead for the construction industry is the use of appropriate materials, energy – saving both in the stage of manufacturing materials and construction of buildings, as well as life, as these are impacting on the environmental, generating impacts related to energy consumption. In this context, the main objective of this research was to identify, using energy consumption data, the best option for building constructive isolated dwellings. Analyzed the literature review, it appears that the relative impacts of energy consumption are significant, and that energy use in summary form allows you to evaluate the environmental impacts of the life cycle of the building through the estimation of energy consumption. A method of Life Cycle Energy Analysis (LCEA) in buildings, using energy as a measure of environmental impact, allows the presentation rates of embodied energy in MJ/kg or MJ/m2. The research was divided into two stages for reaching the desired outcomes: first it was estimated the embodied energy, in three domestically produced materials: brick, steel and cement, and then, in a second step, functional units composite with the construction materials studied were analysed. Indicators of environmental impact energy consumption and CO2 emission, and associated impacts could be characterised at each stage of the life cycle of production of the materials analysed. After this process, it was possible to draw some conclusions that can contribute to the emerging approach to sustainability in the construction industry locally. The main findings were: of the three materials analysed, the brick and associated systems are those that produce less environmental impact, since, energy consumption comes from renewable sources and emissions are lower than those others materials. For steel and concrete the amount of energy required and emissions are higher, and they also haves a significant influence of energy consumed for transport, increasing the values of embodied energy, and, therefore, the impacts on the environment.